Ceramide nanoliposomes augment the efficacy of venetoclax and cytarabine in models of acute myeloid leukemia. Issue 10 (15th September 2022) - Khokhlatchev, Andrei V.; Sharma, Arati; Deering, Tye G.; Shaw, Jeremy J. P.; Costa‐Pinheiro, Pedro; Golla, Upendarrao; Annageldiyev, Charyguly; Cabot, Myles C.; Conaway, Mark R.; Tan, Su‐Fern; Ung, Johnson; Feith, David J.; et al.
Abstract: Despite several new therapeutic options for acute myeloid leukemia (AML), disease relapse remains a significant challenge. We have previously demonstrated that augmenting ceramides can counter various drug‐resistance mechanisms, leading to enhanced cell death in cancer cells and extended survival in animal models. Using a nanoscale delivery system for ceramide (ceramide nanoliposomes, CNL), we investigated the effect of CNL within a standard of care venetoclax/cytarabine (Ara‐C) regimen. We demonstrate that CNL augmented the efficacy of venetoclax/cytarabine in in vitro, ex vivo, and in vivo models of AML. CNL treatment induced non‐apoptotic cytotoxicity, and augmented cell death induced by Ara‐C and venetoclax. Mechanistically, CNL reduced both venetoclax (Mcl‐1) and cytarabine (Chk1) drug‐resistant signaling pathways. Moreover, venetoclax and Ara‐C augmented the generation of endogenous pro‐death ceramide species, which was intensified with CNL. Taken together, CNL has the potential to be utilized as an adjuvant therapy to improve outcomes, potentially extending survival, in patients with AML.